2022
DOI: 10.1186/s43162-022-00111-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sustained virological response after direct-acting antivirals on liver fibrosis in patients with chronic HCV infection

Abstract: Background Direct-acting antivirals (DAAs) have revolutionized the therapy of HCV infection with higher sustained virological response (SVR) rates. Fibrosis regression after achieving SVR to DAA remains to be evaluated in chronic hepatitis C patients. One of the main inquiries here is what occurs with liver fibrosis after achieving a SVR, albeit the current DAA was not intended to be antifibrotic. Liver biopsy was replaced by various non-invasive methods, like FIB4 score and fibroscan. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In consistent with the current study, Reddy et al (13) concluded that the recent antiviral agents were found to improve hepatic functions during short term follow up in particular increase in serum albumin. Such observations have been made during short-term follow-up in many studies as well (14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 87%
“…In consistent with the current study, Reddy et al (13) concluded that the recent antiviral agents were found to improve hepatic functions during short term follow up in particular increase in serum albumin. Such observations have been made during short-term follow-up in many studies as well (14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 87%
“…Recent advances in direct acting antiviral development have revolutionized the therapy of HCV infection. However, a sustained virological response in a significant proportion of patients does not reverse liver pathology [45,46]. Pathological mechanisms in liver fibrosis and cirrhosis in HCV patients [47,48], and in vivo models [49], have mainly highlighted the deregulation of inflammatory and metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in direct acting antiviral development have revolutionized the therapy of HCV infection. However, a sustained virological response in a significant proportion of patients does not reverse liver pathology [46,47]. Pathological mechanisms in liver fibrosis and cirrhosis in HCV patients [48,49] and in vivo models [50] have mainly highlighted the deregulation of inflammatory and metabolic processes.…”
Section: Discussionmentioning
confidence: 99%